(3cJGH GdLaQ GdRGjQLI GdSHJjIs - (3CHj GdYHGS CMeO GdSHJj Hf eMeO Hf YKeGf GdCROj GdeQGcTj GdeYQha HGHf GdHfGs
(3ChdgG (B:s
(3LaQ hef gPg GdbhGfjf GdUfGYjI dGSJNQGL GdZjhH ajeG jRYehf GdRGjQLI GdeSeGI HRGjQLI s
(3BNQgG (B:s
(3hZjQg ef afhf GdMceI GdGdgjI hYdjg eOGO hVY GdRjGQL GdMQajI hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3cJGH LaQ ofbd ef ebOeI GHf NdOhfs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdLRQjI GdYGeI (B- (3GdehUd (B(489 (3H(B) s
Keywords: (3GdMQha h GdChaGbs